2018
DOI: 10.1088/1361-665x/aacfe9
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic shearography for crack detection in metallic plates

Abstract: Shearography is an optical non-destructive testing (NDT) technique which is suitable for large area and fast inspections. However, it is difficult to detect cracks in metals by using conventional stress loading methods for shearography, including stress loadings by vacuum, thermal and vibrational excitations, due to the high rigidity and/or the high thermal conductivity of metals. In this work, we propose and demonstrate an acoustic shearography method for detection of cracks in metallic plates. Piezoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The various acoustic wave modes have their own unique purposes, where dispersive waves are useful for localization of defects over larger area and focused waves are better at penetrating deep into the test object. The optimal frequencies to introduce the higher stress loads for enhanced shearography detection are typically the resonant frequencies of the piezoelectric transducers, where the electrical impedance is at its lowest and has the highest efficiency in converting electrical energy to mechanical energy [4].…”
Section: Acoustic Shearography Methodologymentioning
confidence: 99%
“…The various acoustic wave modes have their own unique purposes, where dispersive waves are useful for localization of defects over larger area and focused waves are better at penetrating deep into the test object. The optimal frequencies to introduce the higher stress loads for enhanced shearography detection are typically the resonant frequencies of the piezoelectric transducers, where the electrical impedance is at its lowest and has the highest efficiency in converting electrical energy to mechanical energy [4].…”
Section: Acoustic Shearography Methodologymentioning
confidence: 99%
“…In 2010, Kurtz proposed the concept of directed acoustic shearography [53]. In 2017, Liu et al demonstrated that it was feasible to use acoustic waves as stress loading for shearography testing with a piezoelectric disc transducer [54,55], thus demonstrating the feasibility of such a system. The directed acoustic shearography system consists of a phased array transducer, laser light source, and shearography sensor as shown in Figure 13.…”
Section: Directed Acoustic Shearography For Subsurface Crackmentioning
confidence: 99%
“…Shearography is a highly sensitive optical interferometry method 1 . Because of its large measurement field of view and strong vibration-resistant capability, which most optical interference techniques do not feature, shearography has been increasingly studied and applied in the fields of three-dimensional non-destructive testing, material property analysis, and object vibration pattern recognition [2][3][4] . It is a two-step imaging technique that cannot directly obtain the measured information: it must first extract the phase information from the speckle pattern obtained by a camera at different moments during object deformation, and then the corresponding object deformation information can be obtained 5 .…”
Section: Introductionmentioning
confidence: 99%